2016
DOI: 10.1097/aci.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and perinatal exposure, and the risk of asthma and allergies

Abstract: A diverse range of exposures were associated with allergic disease risk, highlighting the susceptibility of children during the perinatal period. Clinicians should reinforce public health messages concerning maternal obesity, smoking, and breastfeeding. The infant gut microbiome is emerging as an important hypothesis, which may mediate the relationship between many perinatal exposures and allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
(50 reference statements)
0
14
0
1
Order By: Relevance
“…Other epigenetic modifications, such as histone modification, noncoding RNAs, chromatin remodeling, may be responsible for the changes of Treg cells too. Previous researches indicated that classic genetic inheritance4344 and perinatal transfer of maternal mediators (such as allergens, antibodies or cytokines) via placenta or breast milk454647 might also be responsible for maternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Other epigenetic modifications, such as histone modification, noncoding RNAs, chromatin remodeling, may be responsible for the changes of Treg cells too. Previous researches indicated that classic genetic inheritance4344 and perinatal transfer of maternal mediators (such as allergens, antibodies or cytokines) via placenta or breast milk454647 might also be responsible for maternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…2 Postnatal microbial infections have been among the most studied factors and several reports have suggested a modulation of the risk of atopic diseases by childhood infections. 2 A number of prenatal factors, for example, maternal smoking, 12 adverse life events 13 and pre-pregnancy overweight 14 have been associated with increased risk of atopic diseases in the offspring. 2 A number of prenatal factors, for example, maternal smoking, 12 adverse life events 13 and pre-pregnancy overweight 14 have been associated with increased risk of atopic diseases in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…1 Accordingly, extensive data suggest that a variety of environmental exposures in early childhood can influence the development of atopic diseases. 2 Postnatal microbial infections have been among the most studied factors and several reports have suggested a modulation of the risk of atopic diseases by childhood infections. [3][4][5][6][7][8][9][10][11] Recently, it has become increasingly evident that already the in utero environment may be important in the development of atopic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more common in childhood, and most adult asthma originate from childhood indicating that childhood events have an important role in asthma pathogenesis [2–4] . Childhood is an important period for the maturation of the immune system, specific infections may alter immunologic programming, which plays critical role in the progression of allergic airways disease (AAD) [5] . Neonatal infections caused by Streptococcus pneumoniae ( S. pneumoniae ), Haemophilus influenzae, Moraxella catarrhalis can increase the risk of bronchiolitis [6] and preschool asthma [7] .…”
Section: Introductionmentioning
confidence: 99%